2022
DOI: 10.1021/acs.jafc.2c06067
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Research Trends on 3-Monochloropropane-1,2-Diol Esters in Foods

Abstract: 3-Monochloropropane-1,2-diol esters (3-MCPDE) are common food contaminants mainly formed in the edible oil refining process. Due to their potential hazards, 3-MCPDE has become a widespread food safety concern. In this study, CiteSpace and VOSviewer were used to conduct a bibliometric analysis on the 3-MCPDE research papers collected in the Web of Science Core Collection from 1998 to 2022. The results showed that the number of research publications on 3-MCPDE has increased rapidly since 2010. Analysis of the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…Bibliometric research related to DI has been conducted by scholars (AM et al, 2023;Dal & Abu, 2023;Kamarulzaman et al, 2018;Shareefa & Moosa, 2020;Sun & Xiao, 2021;Wei et al, 2022). Bibliometric research on existing DI certainly differs from this study.…”
Section: Introductionmentioning
confidence: 74%
“…Bibliometric research related to DI has been conducted by scholars (AM et al, 2023;Dal & Abu, 2023;Kamarulzaman et al, 2018;Shareefa & Moosa, 2020;Sun & Xiao, 2021;Wei et al, 2022). Bibliometric research on existing DI certainly differs from this study.…”
Section: Introductionmentioning
confidence: 74%
“…By analysing the changes in the number of publications in a given field, it is possible to gain a direct insight into the development and future trends of the field as well as the concentration and active period of research in the field (Wei et al, 2022). Figure 2 shows the temporal distribution of publications in the field of EDOP research.…”
Section: Annual Volume Of Publications and Trendsmentioning
confidence: 99%
“…In this study, the keyword co-occurrence network was clustered by the Likelihood ratio (LLR) algorithm, as shown in Figure 4, and a total of eight main clusters were obtained: "instantaneous desire" (cluster #0), "brand image" (cluster #1), "impact" (cluster #2), "product design" (cluster #3), "mental representations" (cluster #4), "health warning label" (cluster #5), "consumer behaviour" (cluster #6), "mere exposure" (cluster #7). The Modularity Q value of the clustering module obtained from CiteSpace mapping was 0.6346, >0.3, indicating a significant network structure, and the Weighted Mean Silhouette S value was 0.8406, greater than 0.7, indicating that the clustering results were reliable and met the criteria for scientific clustering (Wei et al, 2022). The clustering labels were inductively classified according to the principle of homogeneity and divided into four major research themes, as shown in…”
Section: Keyword Co-occurrence and Clusteringmentioning
confidence: 99%
“…Over the past few decades, a set of bibliometric tools have been developed, among which the most used are Bibliometrix, CiteSpace, and VOSviewer. The integration of them has become a common approach in various fields, including medical field( Chen et al., 2022 ; Pei et al., 2022 ; Wan et al., 2022 ), biomaterials( Zheng et al., 2022 ), and food safety studies( Wei et al., 2022 ), due to their ability to provide more systematic and accurate information. Here, we attempted to quantitatively analyze the publication status, authorship collaboration, research hotspots, and trending topics of FTLs research using bibliometric methods, aiming in provide a comprehensive overview in this field.…”
Section: Introductionmentioning
confidence: 99%